Dynamic characteristics and response research of low-frequency vibration harvester based on diamagnetic levitation. (September 2019) - Wu, Kedi; Su, Yufeng; Zhang, Kun; Gong, Qi
Abstract: A low-frequency vibration energy harvester used to collect environmental vibration is proposed in this paper. The energy harvester mainly includes a diamagnetic stabilized levitation structure and elastic films as the stoppers. The floating magnet maintains a stable levitation in the vertical direction under the action of gravity, magnetic force and diamagnetic force. The elastic film is introduced to build a piecewise linear system which can increase the resonant frequency and extend the operating bandwidth for the energy harvester. The energy harvester prototype is designed, manufactured and tested. During the experiment, the working frequency range is extended from 2.1 Hz to 5.1 Hz under the excitation amplitude of 5 mm. The output voltage increases steadily from 59 mV to 159 mV within this frequency range. The experimental results under different harmonic excitation show that the harvester has the potential to work at a broadband and low-frequency range. The proposed harvester could power micro and intelligent equipment in a low-frequency vibration environment.